2021
DOI: 10.1016/j.bbrc.2020.11.036
|View full text |Cite
|
Sign up to set email alerts
|

Role of the E3 ubiquitin ligase HRD1 in the regulation of serotonin transporter function

Abstract: To elucidate the regulation of serotonin transporter (SERT) function via its membrane trafficking, we investigated the involvement of the ubiquitin E3 ligase HRD1 (HMG-CoA reductase degradation protein), which participates in endoplasmic reticulum (ER)-associated degradation (ERAD), in the functional regulation of SERT. Cells transiently expressing wild-type SERT or a SERT C-terminal deletion mutant (SERTDCT), a SERT protein predicted to be misfolded, were used for experiments. Studies using HRD1overexpressing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…and mutation localization could be one of the reason for the dedication of this huge number of E3 ubiquitin ligases embedded in the ER membrane. Nonetheless, HRD1 has been one of the most studied and best characterized E3 ligase and has recently been identified as a core component of ERAD substrates ubiquitination (Carvalho et al, 2010;Baldridge and Rapoport 2016;Schoebel et al, 2017;Kadowaki et al, 2018;Wu et al, 2020;Taguchi et al, 2021). Loss of HRD1 has been reported to be directly linked to accumulation of amyloid β (Aβ) implicated in Alzheimer Disease (Kadowaki and Nishitoh 2013).…”
Section: Discussionmentioning
confidence: 99%
“…and mutation localization could be one of the reason for the dedication of this huge number of E3 ubiquitin ligases embedded in the ER membrane. Nonetheless, HRD1 has been one of the most studied and best characterized E3 ligase and has recently been identified as a core component of ERAD substrates ubiquitination (Carvalho et al, 2010;Baldridge and Rapoport 2016;Schoebel et al, 2017;Kadowaki et al, 2018;Wu et al, 2020;Taguchi et al, 2021). Loss of HRD1 has been reported to be directly linked to accumulation of amyloid β (Aβ) implicated in Alzheimer Disease (Kadowaki and Nishitoh 2013).…”
Section: Discussionmentioning
confidence: 99%
“…SERT function is regulated by numerous signaling pathways that serve to maintain 5HT homeostasis in accordance with physiological demands. Evidence suggests that SERT is modified via post-translational modifications like phosphorylation, ,, glycosylation, , and ubiquitylation , that serve to coordinate SERT kinetic activity, localization, surface expression, and degradation in platelets, endothelial cells, and serotonergic neurons. ,,,, Previous studies have reported that activation of PKC with β-PMA induces a time-dependent effect on SERT function that occurs in two phases. The first phase occurs at 5 min of PKC activation decreasing 5HT transport capacity without decreasing surface SERT levels, while the second phase occurs 30 min after activation, promoting the internalization of surface SERT .…”
Section: Discussionmentioning
confidence: 99%
“…SERT function is regulated by numerous signaling pathways that serve to maintain 5HT homeostasis in accordance with physiological demands. Evidence suggests that SERT is modified via post-translational modifications like phosphorylation (1,3,28), glycosylation (4,5), and ubiquitylation (29,30) that serve to coordinate SERT kinetic activity, localization, surface expression, and degradation in platelets, endothelial cells, and serotonergic neurons (1)(2)(3)6,28,31,32). Previous studies have reported that activation of PKC with b-PMA induces a timedependent effect on SERT function that occurs in two phases.…”
Section: Discussionmentioning
confidence: 99%